Visual–Spatial Ability Predicts Academic Achievement Through Arithmetic and Reading Abilities - Liu, Saifang; Wei, Wenjun; Chen, Yuan; Hugo, Peyre; Zhao, Jingjing (Frontiers in Psychology, 2021)
This study aimed to investigate how visual-spatial ability predicted academic achievement through arithmetic and reading abilities. Four hundred and ninety-nine Chinese children aged from 10.1 to 11.2 years were recruited and measured visual-spatial, arithmetic and reading abilities. Their mathematical and Chinese language academic achievements were collected for two consecutive school years respectively, during the same year as cognitive tests and one year after the cognitive tests. Correlation analysis indicated that visual-spatial, arithmetic, and reading abilities and academic achievements were significantly correlated with each other. The SEM analyses showed that there were two paths from visual-spatial ability to academic achievement: a major path mediated by arithmetic ability and a minor serial mediation path from visual-spatial ability to arithmetic ability to reading ability, then to academic achievement. Results shed light on the importance of visual-spatial in education.